Knowledge and Practices of Heart Failure Patients Related to diet - زريق, علي (Latakia University Journal -Medical Sciences Series, 2021)
Heart failure is defined as an abnormal condition that includes the failure of the heart pump to pump blood throughout the body optimally and it represents 23% of all diseases affecting the heart, eating a healthy diet helps prevent and treat this disease. The dietary information and practices of patients with chronic heart failure are the key to the treatment plan, especially for patients with advanced complications. And for that, the present study was conducted on a sample of 50 patients with heart failure. The results showed that (74%) of the patients in the study had a good level of knowledge related to their diet, and (52%) of them have an average level of practices related to this diet, the researcher recommended to continuously monitor and follow up the knowledge and practices of heart failure patients in order to evaluate them continuously.